An evaluation of different extensive wildlife production systems in the Western Cape Province of South Africa - Van Hoving, Susanna Catharina Petronella (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Agricultural Economics))--University of Stellenbosch, 2011.